(untitled) (Papeles, 2022)
The Argentine legal system regulates the damages derived from anticompetitive practices through different legal norms. The objective of this article is to trace and identify various provisions that regulate the cases of damages that are the consequence of anti-competitive practices carried out by companies within the framework of their performance in the market.